2007
DOI: 10.1016/j.ijsolstr.2006.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the failure mode and softening behaviour of sands in true triaxial tests

Abstract: This paper presents a theoretical analysis and a numerical study of the failure mode in sands based on a hypoplastic description of the material. A bifurcation analysis is performed to study the failure mode in sands under true triaxial stress conditions at the material response level. It is shown that either uniform failure or localized failure can occur, depending on the intermediate principal stress. Uniform bifurcation occurs in tests along stress paths with a lower Lode angle, including the stress path fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…The numerical model presented in this paper can reasonably mimic the configuration of true triaxial compression apparatus. As noted by Huang et al [39], this approach can effectively control the specimen to deform uniformly and thus lead to realistic averaged stressstrain-dilation relationships. The particle properties, such as particle size distribution and contact stiffness are listed in Table 3.…”
Section: Model Configuration Of Triaxial Compression Testsmentioning
confidence: 94%
“…The numerical model presented in this paper can reasonably mimic the configuration of true triaxial compression apparatus. As noted by Huang et al [39], this approach can effectively control the specimen to deform uniformly and thus lead to realistic averaged stressstrain-dilation relationships. The particle properties, such as particle size distribution and contact stiffness are listed in Table 3.…”
Section: Model Configuration Of Triaxial Compression Testsmentioning
confidence: 94%
“…Recent experimental and theoretical studies [29,30] demonstrated that uniform critical state may be achieved in a granular sample in trithe characteristic mean stress, it is reasonable to assume that failure friction angle for loose sand is a good approximation of the critical friction angle. Then these results indicate that the critical friction angle is constant for mean stress less than a characteristic value, which marks the starting of substantial particle crushing.…”
Section: Figurementioning
confidence: 99%
“…Critical state under 3-dimensional stress condition is difficult to obtain. In shear tests along stress paths with a Lode angle other than that for triaxial compression, localization in the sample is almost inevitable to occur [30] . This has been the major hindrance for the measurement of critical states.…”
mentioning
confidence: 99%
“…Failures of soil primarily encompass two types, i.e., the tension and shear failures. In a few situations, the cracks in the soil mass caused by the tensile stresses may be of practical importance; while in the stability analysis for most engineering problems, only the resistance against shearing is taken into consideration (Huang et al 2007;Lade 2002). The shear resistance of soil governs the stability of a natural soil slope or a filling structure such as the earth dam, embankment or breakwater, and even the formation and evolution of a landslide (Li et al 2013;Liu et al 2006;Oyanguren et al 2008;Xu et al 2011).…”
Section: Introductionmentioning
confidence: 99%